Intravitreal Injections: Improving Sustainability by Reducing Clinical Waste - Birtel, Johannes; Hammer, Maximilian; Feltgen, Nicolas; Pauleikhoff, Laurenz; Ong, Ariel Yuhan; Geerling, Gerd; Spitzer, Martin S.; Charbel Issa, Peter (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Intravitreal injections are one of the most commonly performed ophthalmic procedures. It is estimated that over 1 million intravitreal injections are performed in Germany annually. The aim of this study was to quantify the waste and carbon footprint associated with single-use injection sets, and to establish a waste reduction strategy.Material and Methods The clinical waste and associated carbon footprint from standard disposable injection sets used by tertiary referral centres in Germany (n = 6) and the United Kingdom (n = 2) were assessed. The safety of performing intravitreal injections with a minimalistic material-sparing approach was evaluated.Results The average weight of an injection set (and hence the waste generated from each injection) was 165 g. On average, each injection set comprised 145 g (88%) of plastic, 2.1 g (1.3%) of metal, 4.3 g (2.6%) of paper, and 12.9 g (7.8%) of gauze/swabs. The production of such injection sets was extrapolated to a CO2 equivalent of 752.6 tonnes (t), and the incineration of the resulting waste to a CO2 equivalent of 301.7 t. For 1 million injections, this equates to 145.2 t of plastic, 2.1 t of metal, 4.3 t of paper, and 12.9 t of gauze/swabs. A material-sparing approach can reduce injection set-associated waste by 99% without necessarily compromising patient safety.Conclusion A resource-saving approach to intravitreal injections can minimise the generation of clinical waste and its associated carbon footprint, thereby supporting sustainability.
Keywords: ophthalmology; sustainability; climate change; intravitreal injection; waste; CO2